Development of a Novel Questionnaire for the Traditional Chinese Medicine Pattern Diagnosis of Stress - Shuai Zheng; Christine Kim; Peter Meier; David Sibbritt; Chris Zaslawski (Medical Association of Pharmacopuncture Institute, 2017)
Currently, there is no definitive diagnosis or list of signs and symptoms for "stress" in either modern biomedicine or Chinese medicine (CM). While modern theories on stress relate to the neurological interaction of a stressor or stimuli on the autonomic nervous system, it is generally regarded as subjective in nature and as such each individual will likely present varying somatic or cognitive signs and symptoms. A questionnaire was therefore developed, based on textual research, that incorporated both general as well as gender specific signs and symptom responses to determine the most common CM patterns associated with individuals who report as feeling stressed. For the 45 females who completed the questionnaire, the mean percentage of symptoms per CM pattern showed that the pattern with the highest average percentage was heart qi deficiency (61.88%) followed by liver blood deficiency (60.23%) and then heart blood deficiency (60.12%). For males (n = 16), heart qi deficiency was also the highest scoring CM pattern with a scoring percentage of 54.81%. In males, however, heart blood deficiency was second with 53.29% followed by liver blood deficiency with 51.10%. Of the general non gender-specific symptoms collected (n = 65 symptoms), the symptom most commonly reported by both men and women was "anxious or racing thoughts", followed by "constant worrying" and "inability to concentrate". The CM diagnostic pattern results may prove useful for clinicians as the change in diagnostic understanding will also modify the treatment principle and subsequent treatment with acupuncture or herbal medicine. Future CM research studies should consider including the questionnaire either as a diagnostic aid or as an outcome measure for acupuncture or herbal medicine studies related to stress.